Factores que influyen en la rentabilidad de las micro y peque\~nas empresas en tiempos de contingencia; Factors that influence the micro and small enterprises profitability in times of contingency - Araceli Hernández Jiménez; Marisol Cáceda Quispe (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The objective of this research is to analyze the factors that influence the profitability of Micro and Small Enterprises in Peru, in the face of the problems derived from Covid-19, with the purpose of contributing to the literature on the study of business behavior during crises, from the perspective of the contingency theory. In order to carry out the research, a quantitative study was carried out with a sample of 291 companies in the commercial and service sector in Lima, Peru. The results of the logistic regression analysis show that only two groups of variables were significant: environment and size, while the group of variables that influence technology was not significant in generating the profitability of the company.
Keywords: L19; L21; L25; M10; 330; Contingency theory; Covid-19; Companies in the commercial and service sector